The analysis of the main directions for reducing the intensity of mass flows of the working fluid through leaks in the working chamber of a piston long-stroke low-speed compressor stage - V. L. Yusha; S. S. Busarov; A. V. Nedovenchany (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The working processes and integral characteristics of piston long-stroke low-speed compressor stages are considered. Well-known technologies for increasing the feed rate are considered as objects of comparison: selection of the main dimensions and parameters of the stage; changing the size and design of valves, using elastomeric structural materials; change in the design of the cylinder-piston seal; changing the layout of the suction valve in the working chamber. Indicator efficiency, supply coefficient and tightness coefficient, as well as discharge temperature are considered as integral indicators. The following independent parameters are considered: parameters of the state of the working fluid at suction, discharge pressure, main dimensions and parameters of the stage, distance from the suction valve to the top dead center, seat diameters of the suction and discharge valves, as well as physical and mechanical properties of structural materials. A comparative analysis of the efficiency of the working process of the stage under consideration is carried out using various technologies for reducing the intensity of mass transfer through leaks in the working chamber of a low-speed, long-stroke piston stage. An assessment is made of the achievable value of the feed coefficient with the combined use of various technologies. The features of the working processes of the object under consideration and the relationship between the intensity of mass flows of working gas through leaks in the working chamber of the stage and the technologies used have been studied. The presented results of the theoretical analysis reflect the nature of the change in the integral characteristics of the stage depending on the technologies used to reduce the intensity of mass transfer through leaks in the working chamber of the stage under consideration.